Fabricação de amostras maciças da liga Fe-Co-B-Si-Nb com estrutura amorfa pela rota de atomização e extrusão a quente - Santana, Diego de Araujo (2018)
Metallic glasses alloys are a relatively new class of materials characterized by the absence of structural long-range order. During heating, these alloys exhibit a glass transition at a temperature (Tg) before reaching the crystallization temperature (Tx). Within this temperature interval (ΔTx = Tx - Tg), they behave as a supercooled-liquid and their viscosity decrease around 6 orders of magnitude compared to the value observed at room temperature. This feature opens up possibilities for consolidation of atomized powders with amorphous structure when it is carried out within ΔTx. In this sense, the present work aimed to study the fabrication of bulk parts of Fe43.2Co28.8B19.2Si4.8Nb4 metallic glass by a combination of gas atomization and hot extrusion. Two gas atomizations were carried out by means of a modified spray forming equipment. Due to the availability of an ingot of the Fe43.2Co28.8B19.2Si4.8Nb4 alloy produced from elements of commercial purity, this material was used for the first atomization. Subsequently, an ingot was produced using high purity elements in a vacuum induction furnace and it was used as feedstock for the second atomization. The atomizations were not able to produce powders with 100% amorphous structure, but produced powders with proper particle size and morphology to be used for consolidation experiments. The powders were deformed within their supercooled liquid interval, producing samples with a diameter of 7.5 mm. The particles were highly deformed, suggesting that they underwent a homogeneous deformation. However, cracks were observed in the samples. The crystalline fraction in the extruded bodies was similar to that observed in the powders.